The Relationship between Islamic Theology and Artificial Intelligence: Challenges and Opportunities - Syafieh Syafieh; Arifin Zain (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
The development of Artificial Intelligence (AI) has brought significant changes to various aspects of human life, including education, social, economic, and religious fields. This phenomenon raises fundamental questions about the relationship between intelligent technology and Islamic theology, a scientific discipline that addresses the relationship between humans, God, and the universe. This article analyzes the relationship between Islamic theology and Artificial Intelligence, highlighting the challenges and opportunities that arise in contemporary Muslim society, particularly within the State Islamic Religious Colleges (PTKIN). The research method used is a literature review with a normative-philosophical approach and a conceptual analysis of Islamic theological literature and studies on the ethics of technology. The results of the study indicate that AI poses theological challenges regarding the authority of knowledge, humanitarian ethics, and the meaning of moral responsibility. However, AI also opens strategic opportunities for the development of contextual Islamic theological studies, for strengthening humanitarian values, and for integrating science and religion within PTKIN. This article emphasizes the crucial role of Islamic theology in providing an ethical and spiritual framework for the responsible development and utilization of AI.